Therapeutic games for the treatment of flat feet in children aged 4 to 5 years - Ricardo Antonio Valdés-Llossas; Lourdes Utria-Figueroa (Universidad de Guantánamo, 2011)
The game is the activity that attracts the child and is very important for their development. Through this, the small discover relationships that exist between people objectively understand that participation in every activity of man requires compliance with certain obligations, and gives you a number of rights. In the investigative work offers practitioners of physical culture and sport a tool to improve care for children with flat feet Grade 1 is relaxed so that the treatment of this deformity which means a challenge for physical culture therapeutics. To carry out the research were used the following methods the theoretical level, the empirical, the mathematician.